Genomic analysis of serogroup Y Neisseria meningitidis isolates reveals extensive similarities between carriage-associated and disease-associated organisms - Oldfield, N; Harrison, O; Bayliss, C; Maiden, M; Ala'Aldeen, D; Turner, D (Oxford University Press, 2016)
Neisseria meningitidis is a frequent colonizer of the human nasopharynx, with asymptomatic carriage providing the reservoir for invasive, disease-causing strains. Serogroup Y (MenY) strains are a major cause of meningococcal disease. High-resolution genetic analyses of carriage and disease isolates can establish epidemiological relationships and identify potential virulence factors.Whole-genome sequence data were obtained for 99 MenY carriage isolates recovered in the United Kingdom during 1997-2010. Sequences were compared to those of 73 MenY invasive isolates recovered during 2010-2011, using a gene-by-gene approach.Comparisons across 1605 core genes resolved 91% of isolates into one of 8 clusters containing closely related disease and carriage isolates. Six clusters contained carried meningococci isolated during 1997-2001, suggesting temporal stability. One cluster of isolates, predominately sharing the designation Y: P1.5-1,10-1: F4-1: ST-1655 (cc23), was resolved into one subcluster with 86% carriage isolates and a second with 90% invasive isolates. These subclusters were defined by specific allelic differences in 5 core genes encoding glycerate kinase (glxK), valine-pyruvate transaminase (avtA), superoxide dismutase (sodB), and 2 hypothetical proteins.High-resolution genetic analyses detected long-term temporal stability and temporally overlapping carriage and disease populations for MenY clones but also evidence of a disease-associated clone.